Regulating Pet Insurance in Indonesia - Ermanto Fahamsyah; Iswi Hariyani; Ance Rimba (Lentera Hukum, 2020)
Nowadays Indonesia has not had a regulation on pet insurance. Meanwhile, in practice, there already are some pet insurance products. This gap has led to pet insurance policies that are only being based on general contract regulations and principles. One of the general contract principles is the consensual principle which is outlined in Article 1320 paragraph 1 of the Civil Code. The research of this paper is conducted based on pet insurance regulations, principles and norms application. It concludes that pet insurance policies that are being based only on the consensual principle have binding legal force as regulated on Article 1338 of the Civil Code. The conception of pet insurance in Indonesia subsequently should refer to the Ministerial Regulations, such as the Regulation of Minister of Agriculture Number 40/Permentan/SR.230/7/2015 regarding Agriculture Insurance Facility and also other supplementary regulations. Keywords: Pet Insurance, Insurance Law, Insurance Contracts.